Prospecção química do extrato etanólico das folhas de Plectranthus ornatus Codd - Mesquita, Lidivânia Silva Freitas (2019)
This work reports the chemical study of the ethanol extract from leaves of Plectranthus ornatus Codd (lamiaceae), whose goal was to isolate new bioactive secondary metabolites. Using conventional methods of chromatography were isolatted eight diterpenes, being three clerodanes [11-acetoxy-2-oxo-neocleroda-3,13E-dien-15-oic acid (PO-1), 2-oxo-neocleroda-3,13E-dien-15-oic acid (PO-3) and 11R*-acetoxy-2-oxoneocleroda-3,13E-dien-15-oic methyl ester (PO-12)], and five abietanes [7,12S*,17- triacetoxy-6R*,19-dihydroxy-abiet-8-ene-11,14-dione (PO-2), 12R*-acetoxy-3R*,6S*,7-trihydroxy-13,16-abiet-8-ene-11,14-dione (PO-7), 6S*,12R*-diacetoxy-3S*,7-dihydroxy-13,16-abiet-8-ene-11,14-dione (PO-6), 3S*,17-diacetoxy-6,11,12,14,16-penta-hydroxy-5,8,11,13-abietatetraen-7-one (PO-9), and 3-acetoxy-6,11,12,14,16-penta-hydroxy-5,8,11,13-7-one (PO-8)]. In addition, were isolated the caffeic acid (PO-4), the flavonoids pedalatin (PO-5) and circimaritin (PO-10), and a ceramide (PO-11). Their structures were elucidated by interpretation of their spectroscopic data (IR, HRESIMS and 1H and 13C NMR) and by comparison with published data of analogous compounds. The compounds compostos PO-1, PO-2, PO-5, PO-6, PO-7, PO-8, PO-9, PO-10 e PO-11were assayed on four cancer cell lines [SF-295 (glioblastoma), PC-3 (prostate), HCT-116 (colon) e HL-60 (leukemia)]. Except PO-5, which was moderately cytotoxic against the cell lines SF-295 (CI50 4,15 µg/mL) and HL-60 (CI50 4,16 µg/mL),all the compounds were inactive.